Pemberdayaan Masyarakat Dengan Program Pelatihan Penguasaan Tekhnologi Demi Membangun Lingkungan Hidup Yang Berkelanjutan Di Desa Gemblengan, Garung, Wonosobo - Faizah Inayati; Evi Salami; Dhiyah Kurniawati; Inda Fitriana; Nindy Silvia; Istianah Istianah; Muhammad Fatah; Ahmad Khasif Khusaini; Fajar Fajar; Bait Askhabul Kahfi (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
The digital era has brought various good changes as a positive impact that can be used as well as possible. But at the same time, the digital era also brings many negative impacts, so that it becomes a new challenge in human life in this digital era. Challenges in the digital era have also entered various fields such as politics, economy, socio-culture, defense, security, and information technology itself. Apart from the notion of method, of course in carrying out research using descriptive research methods with a qualitative approach. A research procedure in which descriptive data is presented in some written or spoken words from observable people or actors. In qualitative research the data collected is not numbers, but in the form of words or arguments. The data in question comes from interviews, field notes, and others. For business actors or the trading sector, digitalization is considered very important to minimize operational costs and to reach more consumption. People become more aware of how to operate the internet to make it easier to access additional information related to lessons or just to add insight. Facilitate costs and time in public services so that public services to the community become faster. Technology in the digitalization era is marked by the increasingly massive penetration of social media in various aspects of economic, political, cultural and defense and security life. This change is a consequence of changing communication patterns towards digitizing communication using contemporary social media channels. Therefore, technology training is very important so as not to be left behind by the current development of the times.